GEOGRAPHY AND THE TEACHER and ELEMENTARY SCHOOL GEOGRAPHY (Author: John H. Wise) - Lloyd, Trevor (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1966)
John H. Wise. Geography and the Teacher. Brisbane: The Jacaranda Press, 1%6, 243 pp. Appendices. Index. John H. Wise, et al. Elementary School Geography, a Handbook of Ideas. Montreal: West Island School Board, 1966, n.p., mimeo.